The prognostic value of selective neck dissection in early-stage major salivary gland carcinoma: a population-based analysis - An, Meiyu; Zuo, Jiaxin; Yuan, Fang; Xiong, Ping (Frontiers in Oncology, 2024)
Objective: This population-based study aims to assess the survival benefits of selective neck dissection (SND) compared to neck observation in patients with T1/T2N0M0 major salivary gland malignancy (MSGC). Methods: We conducted a retrospective review of T1/T2N0M0 MSGC patients who underwent primary tumor surgical extirpation with or without elective neck dissection in the Surveillance, Epidemiology, and End Results database (SEER) from 2004-2015. The impact of SND and clinical variables on overall survival (OS) and disease-specific survival (DSS) was evaluated using Univariate and Multivariate Cox proportional hazards regression models. Kaplan-Meier survival curves were generated, and survival rates were assessed via the log-rank test. Results: Of 3778 post-operative T1-T2N0M0 MSGC patients, 2305 underwent elective neck dissection, while 1473 did not. Median follow-up was 106 months. Univariate and Multivariate analysis identified SND as a prognostic factor for OS in all the study population. After stratified analysis, we found that in the poorly high-grade (differentiated and undifferentiated) patients, the survival showed a significant OS and DSS benefit after receiving SND compared with the neck observations [HR for OS (95%CI): 0.571(0.446-0.731), P＜0.001] and [HR for DSS (95%CI): 0.564(0.385-0.826), P=0.003], other than in the well differentiated or moderately differentiated subgroup. Especially, when the pathological is squamous cell carcinoma, the results show that the people underwent SND had better prognosis, not only in OS [HR (95%CI): 0.532(0.322-0.876), P=0.013], but also in DSS [HR (95%CI): 0.330(0.136-0.797), P=0.014]. The multivariate analysis also yielded encouraging results，compared with neck observation, receiving SND bought about a significant independent OS (adjusted HR, 0.555; 95% CI, 0.328-0.941; P=0.029) and DSS (adjusted HR, 0.349; 95% CI, 0.142-0.858; P=0.022) advantage in high grade squamous cell carcinoma MSGC patients. The Kaplan-Meier survival curves also demonstrated that adjusted SND still had significantly better OS(P=0.029) and DSS(P=0.022) than the observation group in patients with high-grade squamous cell carcinoma of MSGC. Conclusions: Poorly differentiated and undifferentiated T1/T2N0M0 major salivary gland malignancy treated with selective neck dissection demonstrated superior survival compared to neck observation, especially in the pathological subtype of squamous cell carcinoma. These findings suggest the potential benefits of multimodal therapy for appropriately selected patients, emphasizing significant clinical implications.